Present Status and Problems for Odor at Residence-Space - OKADA, Seishi; MUTO, Nobuo; NAKAMURA, Tetuya (Journal of Japan Society of Air Pollution, 1993)
With respect to air environment in residential space, carbon dioxide, carbon monoxide, dust, bacteria, etc. have been listed as parameters of pollution until now. The degree of pollution with these parameters and mutual relationship of these parameters have been investigated. There have been also researches and investigations linking these parameters and ventilation as well as epidemiologicalresearches. In recent years under the increasing requirement on comfortable environment, the quality of airhas been evaluated including the odor as a parameter. However, the involvement seems to be only at the beginning. In this review, we will select the following odor from the researches concerning to odor in residential environment and describe the present conditions and problems in these investigations: outline of ventilation, body odor, tobacco odor, cooking odor, building odor, odor attached to room, and odor generated from sump pit.